Depression among cancer patients and its relationship with chemotherapy side effects. (Journal of the College of Basic Education, 2022)
Objectives : to assess the level of depression among cancer patients and thechemotherapy side effects and to find out the significant difference betweendepression level regarding these side effects.Methodology : A descriptive analytical study was conducted on a purposivesample of 50 cancer patients from both sexes who were admitted to Radiationand Neuclur Medicine Hospital in Baghdad for the purpose of givingchemotherapy for the period from April 4th to June 20 th , 2008. A structuredinterview using the Self Care Diary (SCD) of Nail et al (1991) and HospitalAnxiety and Depression Scale (HADS) was implemented for data collection.